Analisis Fatwa DSN MUI No. 140 Tahun 2021 Terhadap Regulasi Dewan Pengawas Syariah pada Produk Securities crowdfunding - Rizka Rahmatillah Zidna; Sayyidah Syafiqoh; Bakhrul Huda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine and analyze the extent of the regulation of the Sharia Supervisory Board on securities crowdfunding products based on the DSN MUI fatwa No. 140 of 2021. The research method used is descriptive qualitative method which is focused on problems based on facts carried out by observation. This research focuses on analyzing data on the Shafiq.id website on the offering of Islamic securities in the form of sukuk through crowdfunding services reviewed through the provisions contained in the DSN MUI fatwa NO. 140 of 2021 concerning Islamic securities offerings through information technology-based crowdfunding services based on sharia principles. The results of this study indicate that the Sharia Supervisory Board (DPS) is tasked with ensuring that all activities in sharia fintech always comply with sharia principles, including in sharia crowdfunding activities. Islamic crowdfunding activities must be based on the spirit of helping in goodness (ta'awun) and must be based on Islamic rules and guided by the Qur'an and As-Sunnah. DPS oversees the information technology-based financing service model to ensure that the form of crowdfunding implementation does not conflict with sharia principles. In addition, DPS adjusts the contract according to the form of sharia crowdfunding that will be used by the parties. DPS is also tasked with providing advice to the parties and, in the event of a dispute, resolving it by consensus or through a sharia dispute resolution institution in accordance with the Fatwa of DSN-MUI.